Investigating structure generated turbulence using an unmanned aerial vehicle: A prelude to optimal ventilation strategies in India's upcoming smart cities. Issue 4 (21st November 2016) - Ghosh, Satyajit; Kochhar, Karan; Sharma, Akash; Kaushal, Shreyaan; Agrawal, Jatin; Garg, Anshul; Kumar, Arnav; Dugar, Yash
Abstract : Purpose: The Government of India is proposing the setting up of several new smart cities in the sub-continent. Being an over-populated country, space is at a premium. In congested areas high-rise buildings afford a solution. The purpose of this paper is to present new research involving architecture and computational fluid dynamics (CFDs) must be done at the screening stage of design plans before new cities are laid out. This is achieved in the present study involving a university residential campus with a population of 29, 000 comprising of an assortment of high-rise buildings in complex terrain. Design/methodology/approach: This paper uses a combination of instrument-fitted drone measurements – (equipped with a barometer, and sensors for obtaining temperature, relative humidity and altitude) along with a computational fluid dynamical analysis to yield deep insights into the ventilation patterns around an assortment of building forms. Findings: This study was conducted in a residential complex in the campus of the Vellore Institute of Technology (VIT) India. Based on the deciphered wind velocity pattern, a human thermal comfort study was also conducted. It was concluded that the orientation of the buildings play a pivotal role in enhancing the ventilation rates inside a building. It was observed that a dominant eddy spanning a radius of approximate 34 meters was responsible for much of the air changes within the rooms – the smaller eddies had an insignificant role. This method of ascertaining eddy structures within a study area comprising of an assortment of buildings is essential for accurate prescriptions of glazing ratios on building facades. Research limitations/implications: The main research implications pertain to the use of smart ventilation methods in built up environments. The study shows how large eddies drive the momentum transfer and the air changes per hour with rooms in high-rise buildings in complex terrain. In monsoon-driven flows, there are well set preferred directions of wind flow and this enables the characterization of the fully eddy structure in the vicinity of tall buildings. Another research implication would be the development of new turbulence closure models for eddy structure resolution for flow around complex building forms. Practical implications: This study introduces a novel protocol at the planning stage of the upcoming residential complexes in proposed smart cities in the sub-continent. The results may well inform architects and structural engineers and help position and orient buildings in confined spaces and also ascertain the optimal glazing ratio, which affects the ventilation pattern. Social implications: The results from this study can be used by town planners and architects in urban conurbations in the developing world. The results may well help lower heating ventilation and airconditioning loads. Energy-efficient buildings in developing countries are necessary because most of these have rapidly growing GDPs with a concomitant increase in energy consumption. Originality/value: This novel study combining instrument mounted drone and CFDs shows for the first time how architects and town planners with a limited budget position and orient a group of buildings in a complex terrain.